Primal fear - Lucchesi, Gary; Hoblit, Gary; Gere, Richard 1949-; Linney, Laura; Mahoney, John 1940- (Paramount Pictures, 1996)
A high-powered Chicago attorney defends a penniless altar boy accused of murdering the local archbishop.